Practicing Perfection: Memory and Piano Performance - Chaffin, Roger; Crawford, Mary; Imreh, Gabriela (London Erlbaum, 2002)
The memory feats of famous musicians seem almost superhuman. Can such extraordinary accomplishments be explained by the same principles that account for more ordinary, everyday memory abilities? To find out, a concert pianist videotaped her practice as she learned a new piece for performance, the third movement, Presto, of the Italian Concerto by J.S. Bach. The story of how the pianist went about learning, memorizing and polishing the piece is told from the viewpoints of the pianist (the second author) and of a cognitive psychologist (the first author) observing the practice. The counterpoint between these insider and outsider perspectives is framed by the observations of a social psychologist (the third author) about how the two viewpoints were reconciled. The CD that accompanies the book provides for yet another perspective, allowing the reader to hear the polished performance. Written for both psychologists and musicians, the book provides the first detailed description of how an experienced pianist organizes her practice, identifying stages of the learning process, characteristics of expert practice, and practice strategies. The main focus, however, is on memorization. An analysis of what prominent pianists of the past century have said about memorization reveals considerable disagreement and confusion. Using previous work on expert memory as a starting point, the authors show how principles of memory developed by cognitive psychologists apply to musical performance and uncover the intimate connection between memorization and interpretation.
Keywords: Performance; Piano; Memory